Cogeneration and district heating networks: Measures to remove institutional and financial barriers that restrict their joint use in the EU-28. (1st June 2015) - Colmenar-Santos, Antonio; Rosales-Asensio, Enrique; Borge-Diez, David; Mur-Pérez, Francisco
Abstract: The aim of this research is to identify actions that dissipate the institutional and financial barriers that are faced by those energy projects which comprise the joint use of district heating networks and cogeneration in the EU-28. From this evaluation, institutional and financial barriers were identified, which included: distinctive competence, fuel price volatility, and much of the current regulatory framework. In order to achieve an effective removal of these barriers, and apart from generic and common actions to all the schemes, such as creating anchor loads, adopting an active marketing strategy by the local authorities, or the proposition of updating some communitarian directives on energy issues; it is also necessary to adopt those actions that respond to the casuistry of each Member State. Such actions will ultimately represent the most effective way to get a generalised implementation of energy projects that include a joint use of district heating networks and cogeneration. Highlights: Barriers to the implementation of DHN with CHP plants in the EU-28 were identified. EU Directives are insufficient to achieve a spread of DHN with CHP plants. Unless a substantial change in the market, a definitive take off is difficult. Removal of DH and CHP barriers is required to achieve the EU-28 2020 targets. An individualised search for measures for each EU-28 country is proposed.